menu search
person

2 Respostas

Explicação passo-a-passo:

Olá, tudo bem?

4 (x-1)(x+4) - (x+2)(x+4) = 3 (x+2)(x-1)​

4(x² + 4x - x - 4) - (x²+4x +2x +8) = 3(x² - x + 2x - 2)

4x² + 12x - 16 - x² -6x - 8 - 3x² + 3x - 6x +6 = 0

3x -18 = 0

3x = 18

x = 18/3

x = 6
thumb_up_alt 0 votos positivos thumb_down_alt 0 votos negativos
Resposta:

-2

Explicação passo-a-passo:

4(x^2+4x-x-4)-(x^2+4x+2x+8)=3 (x^2-x+2x-2)

4x^2+16x-4x-16-x^2-4x-2x-8 = 3x^2-3x+6x-6

3x^2-6x-24 = 3x^2+3x-6

(simplificando)

-6x - 3x = 24-6

-9x=18 (-1)

x= -18/9

x= - 2
thumb_up_alt 0 votos positivos thumb_down_alt 0 votos negativos
...